Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1007/bf02101983
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence comparison of the Adh gene in three drosophilids

Abstract: The alcohol dehydrogenase (Adh) gene has been isolated from Drosophila simulans and D. mauritiana by screening lambda clone libraries of each with a previously cloned Adh gene from D. melanogaster. The isolated lambda clones were subcloned and partially sequenced to determine the relatedness of these species and to examine details of evolutionary change in the structure of the Adh gene. We report the sequence of the first 704 nucleotides of each gene as well as 127 bases in the 5' untranslated region. When the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…We compared the glyceraldehyde-3-phosphate dehydrogenase genes in yeast and C. elegans, two nonmethylated forms, and found that, of 11 CpGs in yeast, a total of 3 (27%) had changed in C. elegans, all to TpG. At the control dinucleotides, 8 (15): there were 46 sites where at least one species had a CpG and only 3 sites (6%) varied between these species. At the control dinucleotides, 9 of 194 sites (5%) varied between these species, which is not significantly different from the frequency of change at the CpG dinucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the glyceraldehyde-3-phosphate dehydrogenase genes in yeast and C. elegans, two nonmethylated forms, and found that, of 11 CpGs in yeast, a total of 3 (27%) had changed in C. elegans, all to TpG. At the control dinucleotides, 8 (15): there were 46 sites where at least one species had a CpG and only 3 sites (6%) varied between these species. At the control dinucleotides, 9 of 194 sites (5%) varied between these species, which is not significantly different from the frequency of change at the CpG dinucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…16 Thus, the DNAprotein interaction in the A+T-rich region of the mtDNA has been conserved over a much longer time than has the nucleotide sequence of the same region.…”
Section: Discussionmentioning
confidence: 99%
“…The close relationship of these species is shown by chromosome banding patterns (Lemeunier and Ashburner, 1976), gel electrophoresis (Gonzales et aL, 1982;Ohnishi et aL, 1983), and DNA sequencing (Bodmer and Ashburner, 1984;Cohn et al, 1984). D. mauritiana appears from biogeographic evidence to have arisen from a population of proto-simulans colonizing Mauritius.…”
Section: Introductionmentioning
confidence: 98%